When patients should seek medical care for minor ailments: Perspectives of first- and final-year pharmacy students - Taylor, Jeff Gordon; Nakhla, Nardine; Aspden, Trudi; Rutter, Paul; Van Amburgh, Jenny (Pharmacy Education, 2023)
Background: Universities are tasked with preparing students to assist the public in managing minor ailments. This study aimed to determine when pharmacy students would refer patients to medical care as an indicator of clinical skill. Methods: First- and final-year students from four schools were surveyed to determine referral timelines for 17 scenarios. Responders also quantified symptom severity and their confidence levels. Results: Students responding to at least three cases were kept for analysis (n = 117). First-year students considered nasal congestion to be low in severity, with painful urination and rectal bleeding deemed more serious, all while considering most cases more serious than upper-year students. Student confidence was generally lower in new students. Referral times showed similar patterns between years and universities. Red eye, painful urination, diarrhoea (child), and Gastro-Oesophageal Reflux Disease (GORD) (unhealthy patient) were referred quicker than nasal allergies and cough. Referrals typically stayed within a two-week window for most situations. Conclusion: Timelines for medical care were similar between years and institutions. As expected, new students assessed cases as more serious and had less confidence than their upper-year colleagues. A concern for the institutions might be the low rate of real-world case exposure within programmes.